Pendekatan Multiperspektif dalam Manajemen Penyakit Asma - Dito Anurogo (MEDICINUS, 2022)
Asthma is a chronic inflammatory disorder of the respiratory tract. This scientific review aims to provide comprehensive explanation about asthma, including epidemiology, etiology, diet and nutrition, genetic and epigenetic factor, pathophysiology, asthma control evaluation, imaging, management, and trend toward novel therapy in the future, such as nanotechnology.